Kliinilise auditi „Iseseisva antenataalse ämmaemandusabi kvaliteet“ kokkuvõte - Põllumaa, Siiri; Teesalu, Pille; Mahla, Marge; Staalfeldt-Rahumägi, Silja; Voogla, Pirjo; Unukainen, Tiina; Joona, Sirli (Eesti Arst, 2017)
Eesti Arst 2017; 96(7):386–389